Euglesa lindholmi Bespalaya & Vinarski & Aksenova & Babushkin & Gofarov & Kondakov & Konopleva & Kropotin & Mabrouki & Ovchankova & Palatov & Sokolova & Shevchenko & Travina & Taybi & Soboleva & Zubrii & Bolotov 2024, comb. nov. - Bespalaya, Yulia V.; Vinarski, Maxim V.; Aksenova, Olga V.; Babushkin, Evgeniy S.; Gofarov, Mikhail Yu.; Kondakov, Alexander V.; Konopleva, Ekaterina S.; Kropotin, Alexander V.; Mabrouki, Youness; Ovchankova, Nadezda B.; Palatov, Dmitry M.; Sokolova, Svetlana E.; et al. (Zenodo, 2023)
Euglesa lindholmi (Starobogatov & Streletzkaja, 1967) comb. nov. (Fig. 9C) Odhneripisidium lindholmi Starobogatov & Streletzkaja, 1967: 256, fig. 69. Type series: The holotype (a separate valve) and three separate valves of paratypes are deposited in ZIN, nos 1 and 2 in the systematic catalogue. Type locality: Russia, Republic of Yakutia (Sakha), Quaternary deposits on the left bank of the Allaikha River (Indigirka River Basin). Material examined: North Asia: Gydan Peninsula, VII.2017, Sokolova & Shevchenko leg., Republic of Yakutia, Yana River Basin, VIII.2019, Zubrii leg., Republic of Buryatia, near Vitim Nature Reserve, Dannoe Lake, VIII.2020, Babushkin leg., in total 29 specimens (lot nos RMBH MSph-737, MSph-370, MSph-569/1, MSph-569/2, MSph-572/1). Description: The shell is small (mean shell length ± SD 3.15 ± 0.03 mm), round-oval in shape (Fig. 9C). The beaks are rounded and prominent, and somewhat offset to the posterior edge of the valves (Fig. 9C). The cardinal tooth of the right valve is thickened on the posterior end. The inner cardinal tooth of the left valve is straight. The outer cardinal tooth of the left valve is thickened, shorter than inner cardinal tooth (Fig. 10C). Comments: The 16S and 28S rRNA sequences of this species have no analogues in GenBank and are more closely related to the E. parvula group (Fig. 2). Previously, several species described from the basin of the Indigirka and Kolyma rivers and also from the Kamchatka Peninsula were assigned to the genus Hiberneuglesa Starobogatov in Dolgin, 1983 (Korniushin 1996, Vinarski and Kantor 2016) with the exception of Euglesa subconventa (Starobogatov & Streletzakaja, 1967), Pisidium indigircence Starobogatov & Streletzkaja, 1967, and Euglesa cor (Starobogatov & Streletzkaja, 1967). Currently, this group is treated as the species E. parvula (Graf and Cummings 2023; MolluscaBase 2023) with the junior synonyms: Euglesa anjuica Starobogatov & Korniushin, 1989, Euglesa kolhymensis (Starobogatov & Streletzkaja, ...